Past and Future Use of Wild Relatives in Crop Breeding. Issue 3 (16th June 2017) - Dempewolf, Hannes; Baute, Gregory; Anderson, Justin; Kilian, Benjamin; Smith, Chelsea; Guarino, Luigi
Abstract : Wild species related to agricultural crops (crop wild relatives, or CWR) can increase the adaptive capacity of agricultural systems around the world. They represent a large pool of genetic diversity from which to draw new allelic variation required in breeding programs. Crop wild relatives have been extremely valuable in adapting crop varieties to changing disease pressures, farming practices, market demands, and climatic conditions. Unfortunately, CWR are a threatened resource and measures need to be taken to protect them, both in the wild and in genebanks. Here, we review how wild species have contributed to the development of improved crop varieties and where efforts must be concentrated to harness their value in the future. Drawing on the results of an extensive literature search, a series of 14 expert consultation meetings, and in‐depth interview with experts on 24 crops, we document the role that CWR play in modern crop breeding. We discuss (i) their past and current use, (ii) advanced breeding methods and technologies that promise to facilitate the continued use of CWR, and (iii) what constraints continue to hinder increased use of CWR in breeding.